2013
DOI: 10.1186/2191-0855-3-37
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan against cutaneous pathogens

Abstract: Propionibacterium acnes and Staphylococcus aureus are cutaneous pathogens that have become increasingly resistant to antibiotics. We sought to determine if chitosan, a polymer of deacetylated chitin, could be used as a potential treatment against these bacteria. We found that higher molecular weight chitosan had superior antimicrobial properties compared to lower molecular weights, and that this activity occurred in a pH dependent manner. Electron and fluorescence microscopy revealed that chitosan forms aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 32 publications
3
20
1
Order By: Relevance
“…The membrane integrity and change in cell morphology were further supported by SEM results which showed that majority of the CFA-treated cells increased in size with irregular morphology and altered membrane integrity. Earlier, it was reported that interaction of positively charged chitosan with the negatively charged cell membrane of bacteria causes bactericidal action [13]. However, the better bactericidal activity of CFA is observed in our study due to the synergistic antimicrobial action of ferulic acid and chitosan on multiple cellular targets in bacteria.…”
Section: Discussioncontrasting
confidence: 66%
“…The membrane integrity and change in cell morphology were further supported by SEM results which showed that majority of the CFA-treated cells increased in size with irregular morphology and altered membrane integrity. Earlier, it was reported that interaction of positively charged chitosan with the negatively charged cell membrane of bacteria causes bactericidal action [13]. However, the better bactericidal activity of CFA is observed in our study due to the synergistic antimicrobial action of ferulic acid and chitosan on multiple cellular targets in bacteria.…”
Section: Discussioncontrasting
confidence: 66%
“…Some studies report low molecular weight chitosan generates a higher inhibition rate against Gramnegative bacteria (i.e., E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa), while the reverse is observed with Gram-positive bacteria -with increased molecular weight generating a greater antibacterial response [26]. This finding was confirmed by another investigation, revealing that that higher molecular weight chitosan had a more pronounced impact against Gram-positive species, Proprionibacterium acnes and S. aureus, than lower molecular weights [27]. This effect was differentiated by comparing chitosan-treated S. aureus (Grampositive) and E. coli (Gram-negative); authors suggest two mechanisms for the differing inhibitory effects: in the case of Gram-positive species, chitosan is able to form a polymeric membrane on the cell surface, preventing nutrients from entering the cell and for Gram-negative species, low molecular weight chitosan Reprinted from [73] with permission from Elsevier.…”
Section: Intrinsic Properties Of Chitosansupporting
confidence: 59%
“…The use of chitosan in food industry for food preservation has already been established (Vasilatos and Savvaidis 2013;Lee and Je 2013). Further, chitosan is an effective antimicrobial (Champer et al 2013), antioxidant (Yen et al 2008) and antifungal agent (Park et al 2008) which was an added advantage for intended functional food applications. Hence in our viewpoint, curcumin encapsulated in nanoassemblies generated by interactions of two different functional food ingredients might have offered added advantage to total nutritive quality of food material in addition to its increased preservative effect by antioxidant mechanism in aqueous system.…”
Section: Introductionmentioning
confidence: 99%